The Feminization of Migration and Indonesia’s Protection Diplomacy for Female Migrant Workers in Malaysia Following the 2022 MoU - Hana Novia; Rifki Elindawati; Ica Cahayani; Rachel Kamilia Faradiba Nibal (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
Indonesian female migrant workers continue to experience structural vulnerabilities, particularly in domestic and informal sectors where legal protection remains limited. These conditions are closely associated with the feminization of migration, which places women in undervalued care and domestic work shaped by gender inequality and uneven labor governance. In response to persistent protection challenges, Indonesia and Malaysia signed the 2022 Memorandum of Understanding (MoU) on the Placement and Protection of Indonesian Domestic Migrant Workers, introducing institutional mechanisms such as the One Channel System (OCS). This study examines Indonesia’s protection diplomacy toward female migrant workers in Malaysia in the post-MoU period (2022–2025). Adopting a qualitative research design informed by a post-positivist perspective, the study employs document and content analysis of bilateral policy documents, official reports and statistics from the Indonesian Migrant Workers Protection Agency (BP2MI), and relevant academic literature on gendered migration and labor vulnerability. The findings show that while the 2022 MoU and OCS signal a formal commitment to improving protection, their implementation remains constrained by structural factors. Persistent reliance on non-procedural migration channels, weak legal recognition of domestic work in the host country, and limited enforcement capacity continue to expose female migrant workers to exploitation, unpaid wages, and restricted access to justice. At the same time, migration also enables women to exercise agency as primary breadwinners, illustrating a duality in which empowerment and vulnerability coexist. The study argues that protection diplomacy centered primarily on procedural regulation is insufficient to address the gendered and structural dimensions of migrant vulnerability. More effective protection requires policy frameworks that integrate gender-sensitive approaches, recognize domestic work as formal labor, and address the broader political–economic conditions underpinning feminized labor migration.